2021
DOI: 10.1101/2021.04.22.21255954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of B.1.1.7 and B.1.351 on COVID-19 dynamics. A campus reopening study

Abstract: The timing and sequence of safe campus reopening has remained the most controversial topic in higher education since the outbreak of the COVID-19 pandemic. By the end of March 2020, almost all colleges and universities in the United States had transitioned to an all online education and many institutions have not yet fully reopened to date. For a residential campus like Stanford University, the major challenge of reopening is to estimate the number of incoming infectious students at the first day of class. Her… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A total of 37 studies reporting on public health measures in relation to VOC were included after screening. The majority of included studies reported on the Alpha VOC (n=32) 24–54. The majority of studies were conducted in Europe (n=12),24 29 30 34 35 39 40 44 47 51 53 55 followed by the UK (n=9),26 28 32 33 36 42 45 50 56 USA (n=9),25 37 38 41 43 48 49 54 57 Brazil (n=3),58–60 Canada (n=1),31 South Africa (n=1),27 Israel (n=1)46 and Japan (n=1)52 (figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 37 studies reporting on public health measures in relation to VOC were included after screening. The majority of included studies reported on the Alpha VOC (n=32) 24–54. The majority of studies were conducted in Europe (n=12),24 29 30 34 35 39 40 44 47 51 53 55 followed by the UK (n=9),26 28 32 33 36 42 45 50 56 USA (n=9),25 37 38 41 43 48 49 54 57 Brazil (n=3),58–60 Canada (n=1),31 South Africa (n=1),27 Israel (n=1)46 and Japan (n=1)52 (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of included studies reported on the Alpha VOC (n=32) 24–54. The majority of studies were conducted in Europe (n=12),24 29 30 34 35 39 40 44 47 51 53 55 followed by the UK (n=9),26 28 32 33 36 42 45 50 56 USA (n=9),25 37 38 41 43 48 49 54 57 Brazil (n=3),58–60 Canada (n=1),31 South Africa (n=1),27 Israel (n=1)46 and Japan (n=1)52 (figure 2). Additional details of each study can be found in the online supplemental material 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations